Perancangan Interior Pusat Aktivitas Anak dan Remaja Berbasis Multiple Intelligence di Surabaya - Larasati Sistha Ardani (Intra, 2017)
The more limited interaction of children with the environment outside their schools because of the changes in parenting and the excessive use of gadgets, is the background of the thought to present an educational-recreational facility as an option to activities in Surabaya. “Interior Design of Multiple Intelligence Based Child and Teen Activity Center in Surabaya” accommodates children and teenagers aged 10-15 years old to interact, develop, and learn in a safe and cozy outside-school-environment. The method used in this design process is design thinking in 6 steps, which are (1) Empathize and Define, (2) Research, (3) Ideate, (4) Prototype, (5) Test, and (6) Implement. The design concept was made with reference to the basic idea of ‘Multiple Intelligence’ (a theory of human intelligences by Howard Gardner, 1983), which is applied to the zoning and grouping of the facility. The design involves children’s and teen’s experience to run activities according to their interest and talent; which the Multiple Intelligence Theory categorized into Logic-Mathematical, Linguistic, Musical-Rhythmic, Naturalistic, Kinesthetic, Visual-Spatial, Interpersonal and Intrapersonal. To complete the facility, there are various supporting facilities such as the lobby, parent’s lounge, back-office, locker room, mini amphitheater and a canteen. The benefits that can be felt by children and teens in Surabaya in the presence of this activity center is the availability of facilities for the development of interests and talents in a positive, aesthetic, and integrated way.